Noncoding RNA in Extracellular Vesicles Regulate Differentiation of Mesenchymal Stem Cells - Yan, Chaoting; Yu, Jinhua (Frontiers in Dental Medicine, 2022)
To achieve a perfect outcome of tissue engineering regeneration, mesenchymal stem cells (MSCs) need a series biological process including differentiating into the ideal target cells. Extracellular vesicle (EV) in microenvironment contribute to determine the fate of stem cells with epigenetic regulation from noncoding RNA (ncRNA). We searched PubMed databases recently by the following keywords: exosome, noncoding RNA, MSC and extracellular vesicles. After excluding of repeated and less relevant articles, we compiled contents and reference of above literatures and derived this review. We focused on package and function of ncRNA (particularly microRNA, miRNA) in extracellular vesicles, and function of MSC-EV modified by ncRNA which favors tissue regeneration embedding potential challenge.